Standardised method for reporting exercise programmes: protocol for a modified Delphi study. Issue 12 (30th December 2014) - Slade, Susan C; Dionne, Clermont E; Underwood, Martin; Buchbinder, Rachelle
Abstract : Introduction: Exercise is integral to health across the lifespan and important for people with chronic health conditions. A systematic review of exercise trials for chronic conditions reported suboptimal descriptions of the evaluated interventions and concluded that this hinders interpretation and replication. The aim of this project is to develop a standardised method for reporting essential exercise programme details being evaluated in clinical trials. Methods and analysis: A modified Delphi technique will be used to gain consensus among international exercise experts. We will use three sequential rounds of anonymous online questionnaires to refine a standardised checklist. A draft checklist of potentially relevant items was developed based on the results of a systematic review of exercise systematic reviews. An international panel of experts was identified by exercise systematic review authorship, established international profile in exercise research and practice and by peer referral. In round 1, the international panel of experts will be asked to rate the importance of each draft item and provide additional suggestions for revisions or new items. Consensus will be considered reached if at least 70% of the panel strongly agree/disagree that an item should be included or excluded. Where agreement is not reached or there are suggestions for altered or new items, these will be taken to round 2 together with an aggregated summary of round 1 responses. Following the second round, a ranking of item importance will be made to rationalise the number of items. The final template will be distributed to panel members for approval. Ethics and dissemination: Ethics approval was received from The Cabrini Institute Ethics Committee, Melbourne, Australia (HREC 02-07-04-14). We plan to use a stepwise process to develop and refine a standardised and internationally agreed template for explicit reporting of exercise programmes. The template will be generalisable across all types of exercise interventions. The findings will be disseminated through peer-reviewed publications and conference presentations.